Student Retention and Persistence in University Certificate-First Programs - Troy Martin; Randall Davies (MDPI AG, 2022)
While access to higher education has grown over the past few years, significant barriers exist for nontraditional students attempting to prepare for and complete postsecondary education. For these students, the traditional methods for acknowledging student achievement do not always work. This research explored the impact of earning professional certificates on nontraditional students' confidence, motivation, and persistence. Specifically, this study evaluated the matriculation rates between two cohorts of students who participated in the online PathwayConnect program. The mixed-method study found that matriculation rates for students who were encouraged to earn a certificate increased compared to those who followed a traditional path. Analysis of these results suggests that earning a certificate increased students' confidence and motivation to persist in school. Students reported that (a) earning certificates represented a significant achievement and encouraged them to earn more, (b) the certificate allowed participants to obtain better employment, and (c) the satisfaction of this accomplishment improved their desire to acquire new skills. This approach seemed to positively impact on the development of a strong support network that helped diminish some of the traditional barriers to matriculation. Institutions seeking to improve matriculation rates and student persistence might consider providing professional certificates programs in addition to current academic offerings.